Cultural Aspects in The Novel Senandung Cinta di Lembah Papua by Pujia Achmad - Desy Ratna Prahastiwi; Juli Yani (INTERACTION: Jurnal Pendidikan Bahasa, 2023)
The purpose of this study is to describe the cultural aspects, values, norms, and arts contained in the Novel Senandung Cinta di Lembah Papua by Pujia Achmad. The research method used is a qualitative descriptive research method, because qualitative research prioritizes the depth of appreciation of the interactions between concepts. The novel describes a long prose essay and contains a series of stories of a person's life with the people around him and highlights the nature of each behavior and the form of the story or stories that are depicted by the characters in fictional events, the value of reason and mind that a person has to develop human power and activity. The focus of this research It is important to clearly define the boundaries of the problem. This research can provide benefits for the scientific development of Indonesian literature, especially in studying Indonesian novels with the study of Sociology of Literature. Humans and society, become objects of natural sciences. Based on the results of the research, it has been concluded that the cultural background aspects contained in the Novel Senandung Cinta in the Valley of Papua have cultural aspects. This aspect contained in the Novel Senandung Cinta in the Valley of Papua describes the beliefs of the ancestors which are the guideline for people's lives as an example of good behavior and are expected to be role models for the people of Papua. In literary works, it can also describe a series of stories of a person's life with the people around him and highlight the behavior of the author of the literary work. For example, novels. The novel is primarily a prose genre, with a length that can more or less fill one or two small volumes depicting real life in a fairly broad plot.